Walnut (Juglans regia L.) leaves: phenolic compounds, antimicrobial activity ans antioxidant potential of different cultivars - Pereira, J.A. (2008)
Different cultivars of walnut (Juglans regia L.) leaves (Cv. Lara, Franquette, Mayette, Marbot, Mellanaise and Parisienne) grown in Portugal, were investigated in what concerns phenolic compounds and antimicrobial and antioxidant properties. Phenolics analysis was performed by reversed-phase HPLC/DAD and 10 compounds were identified and quantified: 3- and 5-caffeoylquinic acids, 3- and 4-pcoumaroylquinic acids, p-coumaric acid, quercetin 3-galactoside, quercetin 3-pentoside derivative, quercetin 3-arabinoside, quercetin 3-xyloside and quercetin 3-rhamnoside. The antimicrobial capacity was screened against Gram positive (Bacillus cereus, B. subtilis, Staphylococcus aureus) and Gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae) and fungi (Candida albicans, Cryptococcus neoformans). Walnut leaves selectively inhibited the growth of Gram positive bacteria, being B. cereus the most susceptible one (MIC 0.1 mg/mL). Gram negative bacteria and fungi were resistant to the extracts at 100 mg/mL. Lara walnut leaves were also submitted to antibacterial assays using 18 clinical isolates of Staphylococcus sp. Antioxidant activity was accessed by the reducing power assay, the scavenging effect on DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and b-carotene linoleate model system. In a general way, all of the studied walnut leaves cultivars presented high antioxidant activity (EC50 values lower than 1 mg/mL), being Cv. Lara the most effective one.